The Mercury Resistance Operon: From an Origin in a Geothermal Environment to an Efficient Detoxification Machine - Boyd, Eric; Barkay, Tamar (Frontiers in Microbiology, 2012)
Mercuric mercury (Hg[II]) is a highly toxic and mobile element that is likely to have had a pronounced and adverse effect on biology since Earth’s oxygenation ~2.4 Gy ago due to its high affinity for protein sulfhydryl groups, which upon binding destabilizes protein structure and decreases enzyme activity, resulting in a decreased organismal fitness. The central enzyme in the microbial mercury detoxification system is the mercuric reductase (MerA) protein, which catalyzes the reduction of Hg2+ to volatile Hg0. In addition to MerA, mer operons encode for proteins involved in regulation, Hg binding, and organomercury degradation. Here, we examine the composition of 272 individual mer operons and quantitatively map the distribution of mer-encoded functions on both taxonomic SSU rRNA gene and MerA protein phylogenies. The results indicate an origin and early evolution of MerA among thermophilic bacteria and an overall increase in the complexity of mer operons and in the sophistication of transcriptional regulation through evolutionary time, suggesting continual gene recruitment and evolution leading to an improved efficiency and functionality of the Mer detoxification system. Consistent with a positive relationship between the evolutionary history and topology of MerA and SSU rRNA gene phylogeneties (Mantel R = 0.81, p < 0.01), the distribution of the majority of mer functions, when mapped on these phylograms, indicates an overall tendency to inherit mer-encoded functions through vertical descent. However, individual mer functions display evidence of a variable degree of vertical inheritance, with several genes exhibiting strong evidence for acquisition via lateral gene transfer and/or gene loss. These data suggest that (i) mer has evolved from a simple system in geothermal environments to a widely distributed and more complex and efficient detoxification system, and (ii) MerA is a suitable taxonomic marker for examining the functional diversity of mer.